POLIMORFISME GEN ALPHA ACTININ-3 (ACTN 3) BERHUBUNGAN DENGAN MUSCLE PERFOMANCE ATLET - Wahyuni, Nila (Sport and Fitness Journal; Volume 7, No.3, September 2019DO - 10.24843/spj.2019.v07.i03.p03, 2019)
Background: The performance of professional athletes is very important for the achievement of athletes. The athlete's performance is influenced by various factors, namely environmental factors such as training, diet and sociocultural. One important factor that also affects the performance of athletes is genetic factor that are currently being studied. One of the genetic factors believed to play a role in athlete's performance is the Alpha Actinin-3 gene (ACTN 3). Purpose : to examine how the Alpha Actinin-3 (ACTN 3) gene polymorphism causes variation among individuals in athletic muscle performance. Method : study literature. Result : The ACTN 3 gene codes for the ?-actinin-3 protein which plays a role in producing a large force of contraction (rapid forceful contraction). The genetic variation of the ACTN 3 gene causes several variants of the ACTN 3 gene that play a role in the athlete's muscle performance. Keywords: Polymorphism, ACTN Gen 3, Muscle performance.